The Very Fairy Princess: Graduation Girl! - Andrews, Julie; Hamilton, Emma Walton; Davenier, Christine (New York : Little, Brown and Company, 2014)
As the school year draws to an end, Gerry has a hard time finding her sparkle knowing that she will say goodbye to her teacher, Miss Pym, and class pet Houdini, and start anew in a classroom where she may not be recognized as a very fairy princess.
Keywords: Change -- Juvenile fiction; Teachers -- Juvenile fiction; Schools -- Juvenile fiction; Princesses -- Juvenile fiction; Change -- Fiction; Teachers -- Fiction; Schools -- Fiction; Princesses -- Fiction